The Creation of a High Relief Sculpture Inspired by Khmer Art and Lamduan Flowers of Si Sa Ket Province - Mala, Pinit; Koonthong, Pratak (Journal of Human and Society, Sisaket Rajabhat University, 2024)
The objectives of this research are 1) To study the lintel patterns of Prasat Sa Kamphaeng Yai in Si Sa Ket Province 2) To create high-relief sculptures from Khmer art and Lamduan flowers in Si Sa Ket Province 3) To analyze high-relief sculptures from Khmer art and Lamduan flowers in Si Sa Ket Province which has content related to beauty and abundance. For this research, we utilized various tools, including preliminary patterns surveys and a non-participant observation model. Data were collected through fieldwork, documentation, and photographs, which were then used for analysis. Synthesize a data prototype sketch and practice creating completed artwork. Research results found guidelines for creating high-relief sculptures from Khmer art and Lamduan as follows 1) Generating ideas for the artwork. 2) Gathering information from the field and studying relevant documents. 3) Analyzing the information related to the creation of high-relief sculptures. 4) Synthesizing the information to prepare a draft, ensuring the arrangement of elements creates unity. 5) Executing the artwork creation process, including preparing a prototype sketch, preparing materials and equipment, crafting molds, casting the print, finishing the details and creating a sculpture inspired by Khmer art and Lamduan flowers. The results of the content analysis reveal themes of beauty and abundance. The work is a high-relief sculpture that showcases artistic elements and a form that embodies the characteristics of Si Sa Ket Province. This serves as a guideline for enhancing the value and significance of works in the commercial art field in the future.